Una comunidad de melancólicos: Cartografías afectivas en dos documentales de Raúl Ruiz y Patricio Guzmán - Irene Depetris Chauvin (Les Cahiers ALHIM)
This article examines the way in which, through the construction of spaces, two Chilean documentaries address diverse problems linked to recent history, at the same time that, from a melancholic affection, make it possible the participation of new generations in a collective processes of repair. Despite differences in aesthetic terms, the spatial logics of Cofralandes (2002) by Raul Ruiz and Nostalgia for the Light (2010) by Patricio Guzmán are part of an exploration of the a post dictatorship social landscape in which the wounds of repression and exile remain still open. Highlighting the process of construction of landscape, playing with the « elasticity » of the scale or merging in the same sequence dissimilar spaces and times, these documentaries question the boundaries between remoteness/closeness and national/alien and point to the critical nature of both cinema and memory. As spatial interventions in the present, these works propose « affective maps » also in a metaphorical sense as they articulate a « community of melancholics ». According to Jonathan Flatley, it is possible to think in the political potential of melancholia, assuming that « melancholizing » does not necessarily imply to fall into a depressive state of paralysis, but can function as the starting point for the rewriting of history. In this sense, Ruiz and Guzman’s displacements offer affective maps » that awaken a sense of belonging in relation to the traumatic past and transform melancholia in a way to be interested in the world